Exiled memories : stories of Iranian diaspora - Sullivan, Zohreh T. (Temple University Press, 2001)
""I feel I am the wandering Jew who has no place to which she belongs. I thought I could settle down, but can't imagine staying. Whenever I bought a bar of soap and two came in the package, I thought there would be no need to buy a package of two because I would never last through the second. Why? Because I knew I was returning to Iran -- tomorrow. So too, I would buy the smallest size of toothpastes and jars of oil. Putting down roots here is an impossibility.""These are the words of one Iranian emigre, driven from Tehran by the revolution of 1979. They are echoed time and again